Good Functional Recovery of Complex Elbow Dislocations Treated With Hinged External Fixation: A Multicenter Prospective Study - Iordens, Gijs I. T. (Clin Orthop Relat Res, 2014)
BACKGROUND: After a complex dislocation, some elbows remain unstable after closed reduction or fracture treatment. Function after treatment with a hinged external fixator theoretically allows collateral ligaments to heal without surgical reconstruction. However, there is a lack of prospective studies that assess functional outcome, pain, and ROM. QUESTIONS/PURPOSES: We asked: (1) In complex elbow fracture-dislocations, does treatment with a hinged external fixator result in reduction of disability and pain, and in improvement in ROM, function, and quality of life? (2) Does delayed treatment (7 days or later) have a negative effect on ROM after 1 year? (3) What are the complications seen after external fixator treatment? METHODS: During a 2-year period, 11 centers recruited 27 patients 18 years or older who were included and evaluated at 2 and 6 weeks and at 3, 6, and 12 months after surgery as part of this prospective case series. During the study period, the participating centers agreed on general indications for use of the hinged external fixator, which included persistent instability after closed reduction alone or closed reduction combined with surgical treatment of associated fracture(s), when indicated. Functional outcome was evaluated using the Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH; primary outcome) score, the Mayo Elbow Performance Index (MEPI), the Oxford Elbow Score, and the level of pain (VAS). ROM, adverse events, secondary interventions, and radiographs also were evaluated. A total of 26 of the 27 patients (96%) were available for followup at 1 year. RESULTS: All functional and pain scores improved. The median QuickDASH score decreased from 30 (25(th)–75(th) percentiles [P(25)–P(75)], 23–40) at 6 weeks to 7 (P(25)–P(75), 2–12) at 1 year with a median difference of −25 (p < 0.001). The median MEPI score increased from 80 (P(25)–P(75), 64–85) at 6 weeks to 100 (P(25)–P(75), 85–100) at 1 year with a median difference of 15 (p < 0.001). The median Oxford Elbow Score increased from 60 (P(25)–P(75), 44–68) at 6 weeks to 90 (P(25)–P(75), 73–96) at 1 year with a median difference of 29 (p < 0.001). The median VAS decreased from 2.8 (P(25)–P(75), 1.0–5.0) at 2 weeks to 0.5 (P(25)–P(75), 0.0–1.9) at 1 year with a median difference of −2.1 (p = 0.001). ROM also improved. The median flexion-extension arc improved from 50° (P(25)–P(75), 33°–80°) at 2 weeks to 118° (P(25)–P(75), 105°–138°) at 1 year with a median difference of 63° (p < 0.001). Similarly, the median pronation-supination arc improved from 90° (P(25)–P(75), 63°–124°) to 160° (P(25)–P(75), 138°–170°) with a median difference of 75° (p < 0.001). At 1 year, the median residual deficit compared with the uninjured side was 30° (P(25)–P(75), 5°–35°) for the flexion-extension arc, and 3° (P(25)–P(75), 0°–25°) for the pronation-supination arc. Ten patients (37%) experienced a fixator-related complication, and seven patients required secondary surgery (26%). One patient reported recurrent instability. CONCLUSIONS: A hinged external elbow fixator provides enough stability to start early mobilization after an acute complex elbow dislocation and residual instability. This was reflected in good functional outcome scores and only slight disability despite a relatively high complication rate. LEVEL OF EVIDENCE: Level IV, therapeutic study.